Intralesional steroid and ultrasound therapy in patients with carpal tunnel syndrome - Hasan, Md. Israt; Ahmed, Syed Mozaffar (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The study aimed to compare the effects of intralesional steroid injection and ultrasound therapy for the treatment of carpal tunnel syndrome. A total 130 patients divided into 2 groups: a) One group (n=65) received intralesional corticosteroid injection along with wrist splint, exercise, naproxen sodium 500 mg tablet and omeprazole 20 mg capsule twice daily for 2 weeks; b) Another group received (n=65) ultrasound therapy (10 min/day, 3 days/week for 4 weeks) along with Wrist splint for 4 weeks, exercises for 4 weeks, naproxen sodium 500 mg tablet and omeprazole 20 mg capsule twice daily for 2 weeks. The patients were followed-up 2 weekly for 4 weeks. The visual analogue score, symptom severity scores and functional status scores were significantly improved within each group at week 2 (p<0.05) and week 4 (p<0.05) except for the symptom severity score at (p>0.05). The improvement in symptom severity scores and functional status scores in the intralesional steroid group was more than in the ultrasound therapy group after 4 weeks.